MoS2-TiO2 coated PVDF-based hollow fiber membranes for permeate flux enhancement in membrane distillation. - Fuzil, Nurul Syazana (Elsevier Ltd., 2023)
In this work, the surface of a PVDF-based hollow fiber membrane was modified by coating MoS2-TiO2 to improve the performance of membrane distillation (MD). The MoS2-TiO2 was first synthesized at different ratios using a one-step hydrothermal process. Then, the PVDF-based hollow fiber membrane was spun at various air gaps and PES was also added as an additive. As 5M5T (50 wt% MoS2 and 50 wt% TiO2) possessed better physicochemical properties and narrow band gap, the 5M5T was mixed with trichloro(octadecyl)silane in (OTS) at various loading to form a dip-coating solution. The PP20 membrane (PVDF + PES) spun at a 20 cm air gap was used as a support for MD due to its high porosity and low membrane thickness. It was observed that the contact angle of the MoS2-TiO2/PP20 membrane increased significantly to 136.8 ± 2.33° when the membrane was coated with 0.2% of 5M5T MoS2-TiO2. The MD performances were investigated via an in-house MD system. The results revealed that the performances of MoS2-TiO2/PP20 membranes were much higher than previously reported membranes due to their enhanced hydrophobicity and porosity properties. It was observed that a higher operating temperature could elevate the permeate flux up to 23.3 kg·m−2·h−1, but less than 0.1% changes in the rejection rate. The results obtained in this work suggest that the MoS2-TiO2 coated on the PVDF-based membrane can overcomes the typical permeability/rejection rate trade-off effect, which can play a significant role in enhancing MD performances.